Социальная ответственность как сфера практической социологии - Катаев, Станислав Львович; Катаєв, Станіслав Львович; Kataiev, Stanislav L. (Східноєвропейський національний університет імені Лесі Українки, 2013)
В обществе ощущается дефицит в понимании функций прикладной социологии, что актуализирует рассмотрение возможности еë использования в процессе реализации программ по социальной ответственности. Движение по направлению корпоративной социальной ответственности позволяет расширить сферу применения труда социологов и облегчить проблему их трудоустройства, то есть создаëт потенциальный рынок для услуг профессиональных социологов, которые должны активнее позиционировать себя как специалисты в сфере социального консалтинга, социального планирования, социальной защиты. There is an urgent problem of knowledge and skills in the practice of sociologists of social life and production. One of the areas of use of sociology is social responsibility. Task Goal of the article is to discuss problems of social responsibility in the context of practical sociology. Corporate Social Responsibility is an important focus of the business today. In this connection there is a need for social consultancy, providing services which can be used by sociologists of knowledge and skills. Knowledge of social scientists should be actively involved in social planning, social security and the performance of research, organizational and advisory function of applied sociology in industry.
Social Responsibility as the Scope of Practice of Sociology
Keywords: социальная ответственность; социология; практическая социология; социальный консалтинг; функция социолога в организации; social responsibility; sociology; applied sociology; social consulting; sociologist function in the organization